2022
DOI: 10.3389/fpsyg.2022.927709
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumers’ intention toward domestic energy-saving vehicles: Some insights from China

Abstract: Policies to promote the usage of energy-saving vehicles (EVs), such as electric vehicles and hybrids, were introduced and implemented in many countries due to increasing awareness of the potential benefits of such vehicles on environmental and energy conservation. However, despite consumers’ claims of their concerns and positive attitudes toward environmental issues, those claims have not been translated into energy-saving vehicles’ purchasing behavior. Prior studies neglected the interrelationship between con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…In developing countries, according to Higueras-Castillo et al [45] and Lé vay et al [48], government-provided Incentives have been shown to stimulate EV Purchase Intention. Moreover, Gunawan et al [37], Bennett and Vijaygopal [49], Lim et al [50], Jaiswal et al [51], and Wang et al [52] have confirmed that attitudes toward EVs significantly influence purchase intention.…”
Section: The Future Research Directionsmentioning
confidence: 92%
“…In developing countries, according to Higueras-Castillo et al [45] and Lé vay et al [48], government-provided Incentives have been shown to stimulate EV Purchase Intention. Moreover, Gunawan et al [37], Bennett and Vijaygopal [49], Lim et al [50], Jaiswal et al [51], and Wang et al [52] have confirmed that attitudes toward EVs significantly influence purchase intention.…”
Section: The Future Research Directionsmentioning
confidence: 92%
“…However, there are various definitions of usability that can be found in past studies (González-Sánchez, Zea, & Gutierrez Vela, 2009; ISO/IEC 25010:2011, 2011). Some researchers demonstrated that usability is linked to the product itself (Nielsen, 2012; Z.-X. Wang et al, 2022) while other studies have shown that usability is connected to users’ experiences (González-Sánchez, Zea, & Gutierrez Vela, 2009; González-Sánchez, Montero Simarro et al, 2009; Lim et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers demonstrated that usability is linked to the product itself (Nielsen, 2012; Z.-X. Wang et al, 2022) while other studies have shown that usability is connected to users' experiences (Gonza´lez-Sa´nchez, Zea, & Gutierrez Vela, 2009;Gonza´lez-Sa´nchez, Montero Simarro et al, 2009;Lim et al, 2019).…”
Section: Usabilitymentioning
confidence: 99%